Titanium dioxide nanoparticles: synthesis, characterisations and aquatic ecotoxicity effects. Issue 3 (16th March 2018) - Mezni, Amine; Alghool, Samir; Sellami, Badreddine; Ben Saber, Nesrine; Altalhi, Tariq
ABSTRACT: Little information is available on the potential ecotoxicity of nanomaterials in the marine environment. In particular, the aquatic ecotoxicity impact of titanium dioxide (TiO2 ) has been rarely reported. To carefully address this issue, we report on the synthesis of TiO2 NPs using solvothermal process. The structure and morphology of the prepared TiO2 nanoparticles were characterised using different techniques. To study the potential ecotoxicity effect of TiO2, antioxidant system of mediterranean bivalves ( Mytilus galloprovincialis ) was used, measuring three oxidative biomarkers (ROS production, SOD activity and GSH/GSSG level). No considerable effect was found in the digestive glands of any of the groups treated with TiO2 with concentration gradients ranging from 1 to 100 mg/L. Thus, the level of the superoxide anion, the activity of an antioxidant enzyme superoxide dismutase (SOD) and the GSH/GSSG ratio showed no significantly differences in digestive glands of all treated groups compared to the control. However, slight modifications were observed in the gills at high concentrations. These results demonstrated that TiO2 appears to exert little toxicity on marine mussels after a short-term exposure at high concentration. However, before considering the use of this nanomaterial in various applications, further complementary studies are required in order to ensure the environmental safety of these NPs.